Alterations in resting cerebrovascular regulation do not affect reactivity to hypoxia, hyperoxia or neurovascular coupling following a SCUBA dive. Issue 9 (19th July 2020) - Caldwell, Hannah G.; Hoiland, Ryan L.; Barak, Otto F.; Mijacika, Tanja; Burma, Joel S.; Dujić, Željko; Ainslie, Philip N.
Abstract : New Findings: What is the central question of this study? What are the characteristics of cerebral blood flow (CBF) regulation following a single SCUBA dive to a depth of 18 m sea water with a 47 min bottom time. What is the main finding and its importance? Acute alterations in CBF regulation at rest, including extra‐cranial vasodilatation, reductions in shear patterns and elevations in intra‐cranial blood velocity were observed at rest following a single SCUBA dive. These subtle changes in CBF regulation did not translate into any functional changes in cerebrovascular reactivity to hypoxia or hyperoxia, or neurovascular coupling following a single SCUBA dive. Abstract: Reductions in vascular function during a SCUBA dive – due to hyperoxia‐induced oxidative stress, arterial and venous gas emboli and altered endothelial integrity – may also extend to the cerebrovasculature following return to the surface. This study aimed to characterize cerebral blood flow (CBF) regulation following a single SCUBA dive to a depth of 18 m sea water with a 47 min bottom time. Prior to and following the dive, participants ( n  = 11) completed (1) resting CBF in the internal carotid (ICA) and vertebral (VA) arteries (duplex ultrasound) and intra‐cranial blood velocity ( v ) of the middle and posterior cerebral arteries (MCA v and PCA v, respectively) (transcranial Doppler ultrasound); (2) cerebrovascular reactivity to acute poikilocapnic hypoxia (i.e. F I O 2, 0.10) and hyperoxia (i.e. F I O 2, 1.0); and (3) neurovascular coupling (NVC; regional CBF response to local increases in cerebral metabolism). Global CBF, cerebrovascular reactivity to hypoxia and hyperoxia, and NVC were unaltered following a SCUBA dive (all P  > 0.05); however, there were subtle changes in other cerebrovascular metrics post‐dive, including reductions in ICA (−13 ± 8%, P  = 0.003) and VA (−11 ± 14%, P  = 0.021) shear rate, lower ICA v (−10 ± 9%, P  = 0.008) and VA v (−9 ± 14%, P  = 0.028), increases in ICA diameter (+4 ± 5%, P  = 0.017) and elevations in PCA v (+10 ± 19%, P  = 0.047). Although we observed subtle alterations in CBF regulation at rest, these changes did not translate into any functional changes in cerebrovascular reactivity to hypoxia or hyperoxia, or NVC. Whether prolonged exposure to hyperoxia and hyperbaria during longer, deeper, colder and/or repetitive SCUBA dives would provoke changes to the cerebrovasculature requires further investigation. Abstract :